Logistikqualifikation und Gamification: Softwareentwicklung und Pilotierung der MARTINA-App - Cordula Meier; Mona Mönnig; Wilhelm Koop; Markus Kleffmann; Thomas Neukirchen; Stefanie Jäger; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2017)
– Logistics commands a huge variety of dynamic developments, driven by techno-logical, organizational as well as market changes. Within this dynamic environ-ment, logistics management demands a competent and flexible workforce, up-dated by current training and qualification tools. Publication of this research paper marks the midpoint of the project 'MARTINA', which does encompass the development of a smartphone-based edugaming-app as well as related efforts towards defining a topical map for ongoing qualification in logistics. While the latter has been the main focus of project work in the first two quarters of 2016, general game design as well as software prototype devel-opment have been taken on since. The prototype is as of 2017 being released in iterative steps, each delivering additional content/and or fixes to issues having been discovered during the user tests now running in parallel. This approach en-sures that the final edugaming-app will be relevant and useful for blue- and white-collar employees. Further benefit is the transferrability of game concepts to mul-tiple upcoming qualification topics. This research paper documents the process of iterative software development applied in the project, technical considerations with respect to conditions given by the android ecosystem as well as the realiza-tion of content-independent transferability. Section four contains extensive review and evaluation from an aesthetics and design studies perspective, while section five provides an outline of upcoming milestones in the project MARTINA (further topics and educational games).
Keywords: 650; Logistik; Betriebliches Bildungsmanagement; Computerspiel; Mobile Anwendung; Softwareentwicklung; Nordrhein-Westfalen